An Islamic Economic Analysis of Illegal Cigarette Trade and Its Implications for Market Justice and Public Welfare - Ahmad Imam Firza Renaldi; Musthafa Syukur (Kartika: Jurnal Studi Keislaman, 2026)
The circulation of illicit cigarettes has become a significant economic and social issue in Indonesia due to its impact on market competition, government revenue, and public welfare. This study aims to analyze the implications of illicit cigarette trade for market fairness and community welfare from the perspective of Islamic economics in Paiton District, Indonesia. A qualitative descriptive approach was employed through in-depth interviews, observations, and documentation involving representatives of the legal cigarette industry, retailers, and consumers. The findings reveal that the illicit cigarette trade creates market distortions by enabling producers to evade excise obligations and regulatory requirements, thereby gaining an unfair competitive advantage. This practice weakens the competitiveness of the legal tobacco industry, reduces government revenue, and threatens the sustainability of the formal tobacco sector. Although consumers benefit from lower prices, the long-term consequences include declining public welfare and reduced employment opportunities. From the perspective of Islamic economics, this practice contradicts the principles of 'adl (justice) and maslahah (public welfare), as it prioritizes individual gain at the expense of collective interests. Therefore, stronger law enforcement, public awareness, and ethical economic practices are essential to promote fair market competition and sustainable social welfare